2020
DOI: 10.1177/0886260520949153
|View full text |Cite
|
Sign up to set email alerts
|

Parents Matter: A Descriptive Study of Parental Discussions With Teens About Violence Prevention and Related Topics

Abstract: In the current article we examined the extent to which parents and caregivers engage in violence prevention and related discussions with their youth and the correlates (i.e., demographics, confidence, modeling of emotion regulation) of these experiences. We also examined the ways in which parents access prevention-related information to aid in these discussions with their youth. Participants were 142 parents/caregivers of a middle or high school-aged youth. Results suggested that adults reported speaking with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…Notably, the experiences of adults from various racial, ethnic, and immigrant groups were central to the study using mixed methods including focus groups (Harris & Linder, 2017). Consistent with recent research by Edwards et al (2022) that found a strong desire among adults with youth in their lives to learn more about sensitive prevention topics like RSV, adults in the current pilot study consistently praised the utility of the DOT-A/F Workshop. Adults and youth found the workshop acceptable, perceived that it had positive impact, and was feasible.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Notably, the experiences of adults from various racial, ethnic, and immigrant groups were central to the study using mixed methods including focus groups (Harris & Linder, 2017). Consistent with recent research by Edwards et al (2022) that found a strong desire among adults with youth in their lives to learn more about sensitive prevention topics like RSV, adults in the current pilot study consistently praised the utility of the DOT-A/F Workshop. Adults and youth found the workshop acceptable, perceived that it had positive impact, and was feasible.…”
Section: Discussionsupporting
confidence: 84%
“…These findings add to the growing body of research that suggests partnering with significant adults in the lives of youth may enhance prevention effectiveness and reduce youths' exposure to RSV (Edwards et al, 2022;Preble et al, 2018;Rizzo et al, 2020). Indeed, theories of prevention effectiveness like inoculation theory describe how families may be uniquely positioned to have the nuanced conversations about risky behavior that can promote healthy choices (Compton & Craig, 2019).…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations